Analysis of Electricity Production and Consumption in the Western Economic Zone of the Republic of Sakha (Yakutia) for Developing an Effective Fuel and Energy Balance - ELYAKOVA, Izabella Damdinovna; BURYANINA, Nadezhda Sergeevna; KOROLUK, Yuri Fedorovich; ELYAKOV, Aleksandr Lvovich; DANILOVA, Larisa Ivanovna; KHRISTOFOROV, Aleksandr Andreevich; NOEVA, Elena Evgenyevna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).07, 2018)
This article gives a comparative assessment of the efficiency of electricity production and consumption in the Western Economic Zone (WEZ) of the Republic of Sakha (Yakutia), following the results of the research work ‘Assessment and the Main Trends in the Change of the Natural and Socio-Economic Status and Human Potential of the Western Economic Zone of the Republic of Sakha (Yakutia)’ within the framework of the program of comprehensive scientific research under the state contract N5329 of August 7, 2017. Based on the analysis, the existing risks of electricity supply in the WEZ areas are identified, and recommendations for effective electricity consumption and production in the WEZ areas are developed. The study makes it possible to develop comprehensive recommendations for increasing the efficiency of electricity production and consumption in the WEZ areas. No similar studies have been conducted for the WEZ of the Republic of Sakha (Yakutia) in the past five years. In this regard, the study is significant because both natural and cost indices of electricity production and consumption are calculated for the first time, and recommendations for effective electricity consumption are given in the context of the WEZ settlements. The study helps to assess the state of energy in the WEZ areas of the Republic of Sakha (Yakutia).